Improvement of thermal performance of existing standard government high-rise office buildings in Malaysia through envelope retrofit - Mohamad, Noor Laily (2020)
In most countries, office buildings make up the largest energy-consuming building type within the commercial sector due to their high operating energy requirements. This study revealed that typical government high-rise office (before up-grading works of ACMV system) in Malaysia are operating at an average BEI of 161 kWh/m2/year, which is higher than the GBI standard for a commercial office building and EPU standard for public buildings (140 kWh/m2/year). Therefore, this study aims to develop a validated model for building envelope retrofit that can contribute to annual energy savings with objectives: 1) to establish a case model from selected case building to help understand the influence of building envelope components on overall building energy consumption; 2) to identify the Energy Retrofit Measures (ERMs) and evaluate their impacts on the level of buildings' energy efficiency; and 3) to develop a systematic approach in optimising building envelope retrofit interventions and identify a range of intervention levels in relation to their energy reduction levels. The study was conducted in two phases: 1) identification of case studies and extraction of their energy-related data to facilitate a simulation study, and 2) simulation of energy performance using IES<VE> software to determine an optimised retrofit intervention strategies. The proposed three levels of interventions with a combination of selected building envelope ERMs were applied to the validated case model. The effectiveness of each intervention level and the ERMs was evaluated by comparing the simulated annual and space cooling energy consumption with the base case model. The simulation results in all levels of retrofit interventions demonstrated compliance with the BEI benchmark margins; 116 kWh/m2/year in minor intervention level, 113 kWh/m2/year in moderate intervention, and 110 kWh/m2/year in major intervention level, respectively. The average reduction of BEI for all intervention levels in comparison with GBI standard was between 23% (minor level) to 27% (major level) and with EPU standard was between 18% (minor level) to 21% (major level). Moreover, the results indicated a lower OTTV value than MS 1525:2014 standards of 50 W/m2; with 40.94 W/m2 for minor level, 39.06 W/m2 for moderate level and 37.90 W/m2 for major level. It was observed that a combination of efficient glazing and opaque wall intervention with suitable external shading devices plays an important role in energy reduction when retrofitting a building envelope. This study provides a methodological framework and staged approach of retrofit interventions with integrated ERMs that can be applied by the building sector in general, and the Government of Malaysia in particular, to improve the thermal envelope performance of existing buildings.